التحكيم في حل نزاعات العقود الإدارية بين الشريعة والقانون الليبي : دراسة مقارنة - محمد، فتحي علي ميلاد
The study aimed to identify arbitration in Libyan law and Islamic law. T The problem that led to this study is that there is a clear conflict of subordination of some Libyan institutions to foreign arbitration centers or bodies that are not local and independent of the Libyan government, which makes the rights of contracting parties vulnerable to being lost. The proposed form of the Libyan arbitration law did not clearly regulate arbitration in administrative contract disputes due to the scattering of legal articles related to arbitration, and the failure to complete the legal formulation that can be relied upon in organizing arbitration. The study highlights the importance of shedding light on the challenges facing the application of arbitration in resolving administrative disputes in Libyan law and ways to treat them in the light of Islamic law. The study followed the analytical approach to analyze arbitration in Libyan law and Islamic law. The study also followed the inductive approach to extrapolate the texts of the Noble Qur’an and the Sunnah of the Prophet regarding arbitration, and the study followed the comparative approach to compare arbitration in Libyan law and Islamic law. The study reached many results, including that the provisions of Islamic Sharia are identical to the Libyan law in the matter of resorting to private arbitration bodies as it saves time, effort and the necessary cost required for the conduct of the lawsuit, taking into account not to give up the possibility of presenting lawsuits before the courts. In order to appeal the arbitration decision and to review once again the case in dispute. The results also concluded that there is no conflict between Islamic Sharia and the provisions of the Libyan Civil Procedures Law, and that the Libyan law coincides with the opinion of the Malikis and Hanbalis in the issue of the arbitrators’ response, and there is no conflict between Islamic Sharia and the Libyan law in the matter of disqualifying the arbitrators from the task of arbitration between the conflicting parties. The study recommended the necessity of developing legal texts on arbitration, discussing the new Libyan proposed arbitration law, and reformulating legal texts to ensure their clarity and simplicity of drafting. It also recommended emphasizing the invitation of legal experts with legal experience in drafting legal articles in order to divide the new arbitration law into sections according to the nature of administrative contracts.